2007
DOI: 10.1177/153244000700700303
|View full text |Cite
|
Sign up to set email alerts
|

Justice for Sale? Campaign Contributions and Judicial Decisionmaking

Abstract: As state judicial campaigns become progressively more expensive and political, judicial candidates have turned more frequently to lawyers and law firms for campaign contributions. Given that lawyers who contribute to judges' campaigns frequently appear before them in court, the potential for a conflict of interest arises. I ask whether judges are more likely to rule in favor of attorneys who provide financial support to their campaigns. Looking at cases decided in the Supreme Court of Georgia's 2003 term, I sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
(27 reference statements)
2
31
0
Order By: Relevance
“…Moreover, regardless of whether the contributions are modeled as endogenous, the estimates suggest that they are significantly associated with judicial decision making. Indeed, throughout the analyses of Table 4 and consistent prior research (e.g., Cann 2007;Kang & Shepherd 2011), the results imply that contributions are endogenous to judicial decision making and that they correspond to judicial votes in the anticipated direction. The estimated effect of advertising, however, differs in the other analyses of Table 4.…”
Section: Columns [1] and [2] Ofsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, regardless of whether the contributions are modeled as endogenous, the estimates suggest that they are significantly associated with judicial decision making. Indeed, throughout the analyses of Table 4 and consistent prior research (e.g., Cann 2007;Kang & Shepherd 2011), the results imply that contributions are endogenous to judicial decision making and that they correspond to judicial votes in the anticipated direction. The estimated effect of advertising, however, differs in the other analyses of Table 4.…”
Section: Columns [1] and [2] Ofsupporting
confidence: 80%
“…Most research on judicial campaign contributions deals with the possibility of reverse causality (i.e., that judges attract contributions from like‐minded groups) by controlling for judicial ideology rather than explicitly modeling the potential endogeneity. An exception is Cann (:289), who uses an instrumental variables approach to analyze the effect of contributions from lawyers.…”
mentioning
confidence: 99%
“…Judges approaching consideration for reappointment exhibit similar behavior (Shepherd 2009 (Cann 2007). Subtle effects of campaign contributions are apt to go unnoticed, however.…”
Section: Electoral Accountabilitymentioning
confidence: 91%
“…Their results suggest that it may be difficult for judges to ignore partisan efforts that enable them to retain their positions (Shepherd & Kang 2011). Similarly, Cann (2007) found that in Georgia, an attorney's campaign contributions influence judicial decisionmaking in the attorney's cases before that judge.…”
Section: Electoral Accountabilitymentioning
confidence: 99%
“…Along these lines, there are a few studies looking at attorney contributions, but the evidence is mixed. Cann's (2002;2007) studies of the Wisconsin (nonpartisan) and Georgia (nonpartisan) Supreme Courts yield contradictory results. He finds a relationship between attorney contributions and favorable decisions in Georgia, but not Wisconsin.…”
Section: Previous Literaturementioning
confidence: 99%